The Influence of Indonesian Religious Youtuber in Socializing Interfaith Dialogue - Zaitun Saftia; Wirman Wirman (Bulletin of Indonesian Islamic Studies, 2025)
This article analyzes the content of religious preaching delivered by Habib Ja'far on YouTube, focusing on interfaith dialogue and its impact on the understanding of diversity among viewers. In Indonesia, which is known for its diversity, intolerance often arises where differences are considered negative and subjective truths are imposed. To overcome this, efforts are needed to raise awareness of the importance of respecting differences. One method that has proven effective is religious preaching through social media, such as that carried out by Habib Ja'far, who emphasized the importance of moderation in religion in a country with high diversity. The main problems in this study: First, how is the message of religious moderation conveyed by Habib Ja'far on YouTube? Second, how do viewers react to the preaching? Third, how much does Habib Ja'far's religious preaching content contribute to shaping the understanding of diversity among viewers? The research method used is qualitative with a content analysis approach, which allows researchers to systematically assess video content and viewer responses through comments on YouTube. The theories applied include religious moderation and digital communication, which are the basis for analyzing the spread of moderation messages in the context of digital platforms. The results of the study show that the positive reaction of the audience to Habib Ja'far's preaching can play a significant role in increasing the understanding of diversity and instilling an attitude of tolerance. Many comments from the audience expressed appreciation for this moderate preaching, which helped them realize the importance of respecting differences. Habib Ja'far's preaching has succeeded in creating an inclusive discussion space where religious diversity is respected, while also demonstrating the potential of social media in effectively disseminating messages of diversity and tolerance in the digital era.